Genetic modulation of mitochondrial NAD+ regeneration does not prevent dopaminergic neuron dysfunction caused by mitochondrial complex I impairment - D’Alessandro, Karis B.; Zampese, Enrico; Blum, Jenna L. E.; Kuusik, Britta; Palmiotti, Alec; Davidson, Shawn M.; Reczek, Colleen R.; Surmeier, D. James; Chandel, Navdeep S. (Frontiers in Cell and Developmental Biology, 2025)
Dysfunction of mitochondrial complex I (MCI) has been implicated in the degeneration of dopaminergic neurons in Parkinson’s disease. Here, we report the effect of expressing MitoLbNOX, a mitochondrial-targeted version of the bacterial enzyme LbNOX, which increases regeneration of NAD+ in the mitochondria to maintain the NAD+/NADH ratio, in dopaminergic neurons with impaired MCI (MCI-Park mice). MitoLbNOX expression did not ameliorate the cellular or behavioral deficits observed in MCI-Park mice, suggesting that alteration of the mitochondrial NAD+/NADH ratio alone is not sufficient to compensate for loss of MCI function in dopaminergic neurons.